High-strength PE composite film and preparation method thereof
Patent Information
- Application Number
- CN202611480611.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-11-03
AI Technical Summary
Existing PE composite films, after being made ultra-thin, lack sufficient tensile strength and puncture resistance, and have limited barrier properties, making it difficult to meet the long shelf-life packaging requirements of products such as high-fat foods.
The high-strength PE composite film with a five-layer structure includes a reinforcing outer layer, a first adhesive layer, a barrier layer, a second adhesive layer, and a heat-sealing inner layer, which are respectively composed of sulfobutyl isophthalate modified copolyester, isophthalamide modified methylpentanediamine adipamide polyamide, and maleic anhydride grafted polyethylene, and are prepared by co-extrusion and corona treatment technology.
It significantly improves the longitudinal and transverse tensile strength of the composite film, reduces oxygen and water vapor permeability, enhances interlayer adhesion stability and heat-sealing performance, and meets the requirements of high-speed packaging and high-temperature sterilization.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-strength PE composite films, and specifically to a high-strength PE composite film and its preparation method. Background Technology
[0002] Polyethylene (PE) composite film, with its excellent flexibility, heat-sealing properties, and cost advantages, has become the most widely used flexible packaging material in the food and pharmaceutical industries. With the rapid development of downstream industries and increasingly stringent environmental requirements, packaging materials are gradually moving towards ultra-thin and lightweight designs, and traditional thick composite films are being replaced by ultra-thin products.
[0003] Existing PE composite films face the following core challenges: First, their mechanical properties are insufficient. The pure PE substrate itself has low strength, and its tensile strength and puncture resistance further decrease after being made ultra-thin, making it prone to damage during high-speed packaging and storage. Second, their barrier properties are limited. Polyolefins are non-polar materials, and their ability to block oxygen and water vapor is inherently limited. Single-layer PE films are insufficient to meet the long shelf-life packaging needs of high-fat foods, meat products, and other products.
[0004] Therefore, developing a PE composite film that combines high strength, high barrier properties, and good process adaptability has become a technical challenge that the industry urgently needs to solve. Summary of the Invention
[0005] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a high-strength PE composite film and its preparation method.
[0006] The objective of this invention can be achieved through the following technical solutions: In one aspect, this application provides a high-strength PE composite film with a five-layer structure, which consists of, from the outside to the inside: a reinforcing outer layer, a first adhesive layer, a barrier layer, a second adhesive layer, and a heat-sealing inner layer; The outer reinforcing layer is made of sulfobutyl isophthalate modified copolyester; the first adhesive layer is made of a first adhesive layer blend; the barrier layer is made of isophthalamide modified methylpentanediamine adipamide; the second adhesive layer is made of maleic anhydride grafted polyethylene; and the heat-sealing inner layer is made of a matrix material.
[0007] The sulfonated butyl isophthalate modified copolyester is prepared by the following steps: Step a1: Sodium dimethyl isophthalate-5-sulfonate and 1,4-butanediol were added to a four-necked flask equipped with a stirrer, thermometer, gas delivery tube and distillation apparatus. Nitrogen gas was introduced for protection. The stirring rate was 140-150 r / min, and the mixture was heated to 180°C at a rate of 2°C / min. Zinc acetate dihydrate was then added, and the reaction was continued with stirring for 3-3.2 h. After the reaction was completed, the mixture was allowed to cool naturally to 80-90°C. While still hot, the reaction solution was poured into anhydrous ethanol, stirred and cooled to room temperature, filtered, and the filter cake was washed three times with anhydrous ethanol. The filter cake was then transferred to a vacuum drying oven and vacuum dried at 55-60°C for 12-13 h to obtain sodium sulfonate monomer. Step a2: Add dimethyl terephthalate and ethylene glycol to a reaction vessel equipped with a distillation apparatus. Replace the air in the vessel three times with nitrogen. Stir at 170-180 rpm and heat to 180°C at a rate of 2°C / min. Add zinc acetate dihydrate and stir. When the collected methanol amount is ≥30g, add sodium sulfonyl butyrate monomer and continue stirring for 30-32 min. Add antimony trioxide and stir for 15-17 min. Close the distillation channel and begin staged heating and depressurization at a rate of 1°C / min. The temperature was increased to 240℃ at a rate of 1℃ / min, while the pressure was reduced to 1 kPa within 30 min. The temperature was then increased to 275℃ at a rate of 1℃ / min, and the pressure was reduced to 100 Pa within 1 h. Finally, the pressure was reduced to below 10 Pa within 30 min. The reaction was carried out at constant temperature and pressure for 2.5-3.5 h. After that, nitrogen gas was introduced to bring the pressure to atmospheric pressure. The mixture was then poured into cold water for quenching, cut into granules, and then vacuum dried at 110-120℃ for 12-13 h to obtain sulfobutyl isophthalate modified copolyester.
[0008] In a preferred embodiment of the present invention, the ratio of sodium dimethyl isophthalate-5-sulfonate, 1,4-butanediol and zinc acetate dihydrate in step a1 is 1-1.2 mol: 6-7.2 mol: 0.6-0.72 g.
[0009] In a preferred embodiment of the present invention, the ratio of dimethyl terephthalate, ethylene glycol, zinc acetate dihydrate, sodium sulfonyl butyl ester monomer, and antimony trioxide in step a2 is 0.5-0.7 mol: 1.20-1.68 mol: 0.040-0.056 g: 9.61-13.45 g: 0.032-0.045 g.
[0010] The m-phenylenediamine-modified methylpentanediamine adipamide is prepared by the following steps: Step b1: Add adipic acid and anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel, and gas delivery tube. Purge with nitrogen for protection and stir for 15-20 min at 25-30℃ and a stirring rate of 300-400 r / min. Then, add 2-methylpentanediamine and m-phenylenediamine dropwise, controlling the dropping rate at 1-2 drops / s, and adjust the pH to 7.6-7.8. After the addition is complete, raise the temperature to 60℃ and continue stirring for 40-42 min. Allow to cool naturally to room temperature and stand for 2 h. Filter and wash the filter cake three times with anhydrous ethanol. Then place in a vacuum drying oven and dry at 55-60℃ for 12-13 h to obtain methylpentanediamine-m-phenylenediamine adipate. Step b2: Add methylpentanediamine-m-phenylenediamine adipate, deionized water, and sodium hypophosphite to a high-pressure reactor. Replace the air in the reactor three times with nitrogen. Stir at 200 rpm and heat to 225°C at a rate of 2°C / min. React for 60-62 minutes, maintaining the reactor temperature. Release the pressure to atmospheric pressure by opening the exhaust valve, purge with nitrogen for 10 minutes, and then cool. Place in a vacuum drying oven and dry at 55-60°C for 12-13 hours. Grind through an 80-mesh sieve. Then... The mixture was placed in a tubular reactor and purged three times with nitrogen. The temperature was then increased to 180°C at a rate of 1°C / min and held at that temperature for 60-62 min. The temperature was then increased to 195°C at a rate of 1°C / min and held at that temperature for 30-32 min. The nitrogen gas was then turned off, and the mixture was evacuated to ≤100 Pa and reacted for 6-6.5 h. After the reaction was completed, the mixture was kept under vacuum and cooled to room temperature. The product was then discharged and vacuum dried at 70-80°C for 24-26 h to obtain m-phenylenediamine modified methylpentanediamine adipamide.
[0011] In a preferred embodiment of the present invention, the ratio of adipic acid, anhydrous ethanol, 2-methylpentanediamine and m-phenylenediamine in step b1 is 1-1.2 mol: 1600-1920 g: 0.85-0.96 mol: 0.2-0.3 mol.
[0012] In a preferred embodiment of the present invention, the ratio of methylpentanediamine-m-phenylenediamine adipate, deionized water and sodium hypophosphite in step b2 is 200-220g: 50-55g: 0.10-0.11g.
[0013] The matrix material is prepared by the following steps: High-density polyethylene and linear low-density polyethylene are added to a high-speed mixer and mixed for 2 minutes at a temperature of 60-65℃ and a speed of 800-1000 r / min. Then, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite are added and mixed for 3 minutes. Then, erucamide and silica are added and mixed for 5-7 minutes. After mixing, the material is discharged and cooled to below 40℃. Then, it is vacuum dried at 80℃ for 4-6 hours to obtain the matrix material.
[0014] In a preferred embodiment of the present invention, the ratio of high-density polyethylene, linear low-density polyethylene, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(2,4-di-tert-butylphenyl) phosphite, erucamide, and silica is 700-770g: 300-330g: 2.0-2.2g: 2.0-2.2g: 3.0-3.3g: 4-4.4g.
[0015] In a preferred embodiment of the present invention, the high-density polyethylene is designated as TAISOX® F200; the linear low-density polyethylene is designated as SECCO® LL0220AA.
[0016] Secondly, this application provides a method for preparing a high-strength PE composite film, comprising the following steps: The sulfonyl isophthalate-modified copolyester was dried in a vacuum drying oven at 120℃ for 12-16 hours; the m-phenylenediamine-modified methylpentanediamine adipamide was dried in a vacuum drying oven at 90℃ for 24-26 hours; and the maleic anhydride-grafted polyethylene was dried in a vacuum drying oven at 80℃ for 4-5 hours. Then, the temperatures for each section were set according to Table 1. The equipment was preheated by idling for 30-32 minutes. Afterward, the filter screen was installed, and the materials were added to the corresponding extruder hoppers. The sulfonyl isophthalate-modified copolyester was placed in extruder No. 1, the first binder layer blend was placed in extruder No. 2, and the m-phenylenediamine-modified methyl... The pentanediamine adipamide was placed in extruder No. 3, the maleic anhydride-grafted polyethylene in extruder No. 4, and the matrix material in extruder No. 5. Each extruder was initially run at a low speed of 15-20 r / min to remove residual material. Then, casting was started, with the cooling roller temperature controlled at 25-30℃, the traction speed at 30-40 m / min, and the winding tension at 15-20 N / m to ensure a smooth film surface without stretching deformation. After that, the corona treatment machine was turned on to treat only the outer surface, with a treatment power of 800W and an electrode spacing of 1.8 mm. The machine was run stably for 30 minutes to obtain a high-strength PE composite film.
[0017] In a preferred embodiment of the present invention, the first adhesive layer blend is prepared by drying maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene in a vacuum drying oven at 80°C for 4 hours. The dried maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene are weighed at a mass ratio of 90:10. 0.2% of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine is added to the blend and mixed in a high-speed mixer at 60°C and 800 r / min for 4 minutes.
[0018] In a preferred embodiment of the present invention, the maleic anhydride-grafted polyethylene is designated as Nanjing Sutai ST-6.
[0019] The beneficial effects of this invention are: This invention discloses a high-strength PE composite film and its preparation method. The process involves drying sulfobutyl isophthalate-modified copolyester, isophthalamide-modified methylpentanediamine adipamide, and maleic anhydride-grafted polyethylene. Temperatures are then set for each stage, and the equipment is preheated by idling. The materials are then added to the corresponding extruder hoppers: sulfobutyl isophthalate-modified copolyester is placed in extruder No. 1, the first binder blend in extruder No. 2, the isophthalamide-modified methylpentanediamine adipamide in extruder No. 3, the maleic anhydride-grafted polyethylene in extruder No. 4, and the matrix material in extruder No. 5. Each extruder initially runs at low speed to remove residual materials, followed by casting and molding, and then the corona treatment machine is activated. By treating only the outer surface, a high-strength PE composite membrane is obtained through stable operation. A sulfonated butyl isophthalate-modified copolyester serves as the reinforcing outer layer, significantly improving both the longitudinal and transverse tensile strength of the composite membrane. Furthermore, its polar sulfonate groups and flexible butanediol segments ensure excellent compatibility with the adhesive layer, guaranteeing interlayer adhesion stability. A m-phenylenediamine-modified methylpentanediamine adipamide serves as the barrier layer, significantly reducing the oxygen and water vapor permeability of the composite membrane, greatly improving its barrier performance, and also assisting in enhancing the overall mechanical strength of the composite membrane. This high-strength PE composite membrane possesses ultra-high mechanical strength, excellent oxygen and water vapor barrier performance, superior interlayer adhesion stability, and reliable heat-sealing performance.
[0020] In the preparation of high-strength PE composite film, a sulfonated butyl isophthalate modified copolyester was first prepared. Sodium dimethyl isophthalate-5-sulfonate and 1,4-butanediol under zinc acetate dihydrate catalysis underwent transesterification, where the methoxy group in the methyl ester structure was replaced by a 4-hydroxybutoxy group, generating sodium sulfonated butylate monomer and removing methanol. Then, dimethyl terephthalate and ethylene glycol under zinc acetate dihydrate catalysis underwent a basic transesterification reaction to generate dihydroxyethyl terephthalate. Next, the aforementioned sodium sulfonated butylate monomer was introduced to participate in copolymerization. Under antimony trioxide catalysis and high temperature and high vacuum conditions, small molecule byproducts were continuously removed through polycondensation, causing the molecular chain to grow, resulting in the sulfonated butyl isophthalate modified copolyester. This copolyester uses a linear polyethylene terephthalate backbone as the framework, randomly introducing butyl isophthalate copolymer units. Sodium sulfonate groups are attached to the benzene ring of the unit as polar side groups, while the butanediol structure introduces flexibility into the backbone. The methylene segment; the butyl isophthalate side group disrupts the regularity of the polyester molecular chain, reducing crystallinity and melting point, enabling co-extrusion with polyethylene and polyamide at the same temperature, avoiding high-temperature degradation of the adhesive layer, film warping, and interlayer temperature difference defects. The sodium sulfonate polar groups on the molecular chain can form hydrogen bonds and covalent bonds with the anhydride groups in maleic anhydride-grafted polyethylene, significantly improving interlayer bonding force and enhancing the overall density and stability of the composite film structure. At the same time, the polyethylene terephthalate main chain provides basic rigidity, and the toughening effect of the flexible butanediol segment allows the modified polyester to simultaneously improve the surface rigidity and tensile strength of the film, and increase the flexibility of the molecular chain. The sodium sulfonate polar groups can also improve the inherent surface energy of the film, reduce the power requirement for corona treatment, significantly enhance ink adhesion, avoid printing peeling and smudging problems, and impart a certain degree of ionic conductivity to the film, reducing static electricity accumulation during high-speed printing and lamination processes, and avoiding dust adsorption and electrical spark risks.
[0021] In the preparation of high-strength PE composite films, a m-phenylenediamine-modified methylpentanediamine adipamide was prepared. First, adipic acid reacts with 2-methylpentanediamine and m-phenylenediamine in anhydrous ethanol to form methylpentanediamine-m-phenylenediamine adipate. Then, the amino and carboxyl groups in the methylpentanediamine-m-phenylenediamine adipate undergo a condensation reaction, removing water molecules and forming stable amide bonds. High pressure inhibits water evaporation, ensuring the reaction proceeds in a homogeneous molten state and avoiding localized overheating and degradation. Subsequently, the free amino groups at the ends of the oligomer prepolymer molecular chains continue to undergo condensation reactions with the free carboxyl groups at the ends of adjacent molecular chains, removing water molecules and forming new amide bonds. This leads to continuous chain elongation and a gradual increase in molecular weight. A high-vacuum environment forcibly removes trace amounts of water generated during the reaction, breaking the equilibrium limitation of the condensation reaction and propelling the reaction towards the formation of high-molecular-weight polyamide. As a barrier layer in composite films, diacid polyamide's high-density amide bonds in the main chain can construct a dense hydrogen bond network. The introduced benzene ring structure can improve the rigidity of the molecular chain and reduce the free volume between molecular chains, which together significantly improves the barrier performance of the composite film against oxygen and water vapor, effectively blocking the permeation of external gases and extending the shelf life of the contents. At the same time, the main chain amide bonds retain excellent thermal stability and can withstand high-temperature sterilization, meeting the requirements of food packaging that requires high-temperature sterilization. The side methyl groups on its molecular chain disrupt the regularity of the polyamide molecular chain, significantly reducing the melting point of the product and enabling co-extrusion with polyethylene and polyester at the same temperature. The side methyl groups can also play an internal plasticizing role, greatly enhancing the flexibility and low-temperature impact resistance of the polyamide, making the composite film less brittle. In addition, the amide bonds and terminal amino groups on the polyamide molecular chain can react chemically with maleic anhydride-grafted polyethylene to form covalent bonds, significantly improving the interlayer bonding force and enhancing the overall density and stability of the composite film structure. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1: This embodiment describes a method for preparing a high-strength PE composite film, comprising the following steps: Step S1: 1 mol of sodium dimethyl isophthalate-5-sulfonate and 6 mol of 1,4-butanediol were added to a four-necked flask equipped with a stirrer, thermometer, gas delivery tube and distillation apparatus. Nitrogen gas was introduced for protection. The mixture was stirred at 140 r / min and heated to 180 °C at a rate of 2 °C / min. Then 0.6 g of zinc acetate dihydrate was added and the mixture was stirred and reacted for 3 h. After the reaction was completed, the mixture was allowed to cool naturally to 80 °C. While still hot, the reaction solution was poured into anhydrous ethanol and stirred and cooled to room temperature. The mixture was then filtered and the filter cake was washed three times with anhydrous ethanol. The filter cake was transferred to a vacuum drying oven and dried under vacuum at 55 °C for 12 h to obtain sodium sulfonate monomer. Step S2: Add 0.5 mol of dimethyl terephthalate and 1.20 mol of ethylene glycol to a reaction vessel equipped with a distillation apparatus. Replace the air in the vessel three times with nitrogen. Stir at 170 r / min and heat to 180°C at a rate of 2°C / min. Add 0.040 g of zinc acetate dihydrate and stir. When the collected methanol amount is ≥30 g, add 9.61 g of sodium sulfonyl butyrate monomer and continue stirring for 30 min. Add 0.032 g of antimony trioxide and stir for 15 min. Close the distillation channel and open the distillation valve. The temperature and pressure were initially increased in stages: the temperature was increased to 240℃ at a rate of 1℃ / min, while the pressure was reduced to 1kPa within 30min. The temperature was then increased to 275℃ at a rate of 1℃ / min, while the pressure was reduced to 100Pa within 1h. Finally, the pressure was reduced to below 10Pa within 30min. The reaction was carried out under constant temperature and pressure for 2.5h. After that, nitrogen gas was introduced to bring the pressure to atmospheric pressure. The mixture was then poured into cold water for quenching and cut into granules (3×3mm). The granules were then vacuum dried at 110℃ for 12h to obtain sulfobutyl isophthalate modified copolyester. Step S3: Add 1 mol of adipic acid and 1600 g of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Purge with nitrogen for protection and stir for 15 min at 25 °C and 300 r / min. Then, add 0.96 mol of 2-methylpentanediamine and 0.3 mol of m-phenylenediamine dropwise at a rate of 1 drop / s to achieve a pH of 7.6. After the addition is complete, raise the temperature to 60 °C and continue stirring for 40 min. Allow to cool naturally to room temperature and stand for 2 h. Filter the mixture and wash the filter cake three times with anhydrous ethanol. Then, place it in a vacuum drying oven and dry at 55 °C for 12 h to obtain methylpentanediamine-m-phenylenediamine adipate. Step S4: Add 200g of methylpentanediamine-m-phenylenediamine adipate, 50g of deionized water, and 0.10g of sodium hypophosphite to a high-pressure reactor. Replace the air in the reactor three times with nitrogen. Stir at 200 rpm and heat to 225°C at a rate of 2°C / min. React for 60 minutes, maintaining the reactor temperature. Open the exhaust valve to release pressure to atmospheric pressure, purge with nitrogen for 10 minutes, cool, and then place in a vacuum drying oven at 55°C for 12 hours. Pulverize. After passing through an 80-mesh sieve, the sample was placed in a tubular reactor and purged with nitrogen three times. The temperature was then increased to 180°C at a rate of 1°C / min and held at that temperature for 60 min. The temperature was then increased to 195°C at a rate of 1°C / min and held at that temperature for 30 min. The nitrogen gas was then turned off, and the system was evacuated to ≤100 Pa and reacted for 6 h. After the reaction was completed, the sample was cooled to room temperature while maintaining a vacuum. The sample was then discharged and vacuum dried at 70°C for 24 h to obtain m-phenylenediamine modified methylpentanediamine adipamide. Step S5: Add 700g of high-density polyethylene (TAISOX® F200) and 300g of linear low-density polyethylene (SECCO® LL0220AA) to a high-speed mixer and mix for 2 minutes at 60°C and 800 r / min. Add 2.0g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2.0g of tris(2,4-di-tert-butylphenyl) phosphite and mix for 3 minutes. Add 3.0g of erucamide and 4g of silica and mix for 5 minutes. After mixing, release the material and cool it to below 40°C. Then, vacuum dry it at 80°C for 4 hours to obtain the matrix material. Step S6: Dry the sulfonated butyl isophthalate modified copolyester in a 120℃ vacuum drying oven for 12 hours; dry the isophthalamide modified methylpentanediamine adipamide in a 90℃ vacuum drying oven for 24 hours; dry the maleic anhydride grafted polyethylene (maleic anhydride grafted polyethylene model: Nanjing Sutai ST-6) in an 80℃ vacuum drying oven for 4 hours. Then, set the temperatures for each section according to Table 1, preheat the equipment by idling for 30 minutes, then install the filter screen and add the materials to the corresponding extruder hoppers. The butyl isophthalate modified copolyester was placed in extruder No. 1. The first binder layer blend (prepared by drying maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene separately in an 80℃ vacuum drying oven for 4 hours, weighing the dried maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene at a mass ratio of 90:10, and adding 0.2% of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine) The following materials were added to a high-speed mixer and mixed for 4 minutes at 60℃ and 800 r / min: m-phenylenediamine-modified methylpentanediamine adipyl polyamide was added to extruder No. 2; maleic anhydride-grafted polyethylene was added to extruder No. 4; and the matrix material was added to extruder No. 5. Each extruder was initially run at a low speed of 15 r / min to discharge residual material. (After discharge, the speed of each extruder was adjusted to a total thickness of 50 μm, with the speed of extruder No. 1 corresponding to a layer thickness of 10 μm, and the speed of extruder No. 2...) (Corresponding to a layer thickness of 5μm, the speed of extruder No. 3 corresponds to a layer thickness of 10μm, the speed of extruder No. 4 corresponds to a layer thickness of 5μm, and the speed of extruder No. 5 corresponds to a layer thickness of 20μm.) After that, casting begins, with the cooling roller temperature controlled at 25℃, the traction speed at 30m / min, and the winding tension at 15N / m to ensure a smooth film surface without stretching deformation. Then, the corona treatment machine is turned on to treat only the outer surface, with a treatment power of 800W and an electrode spacing of 1.8mm. After stable operation for 30 minutes, a high-strength PE composite film is obtained.
[0024] Table 1
[0025] Example 2: This embodiment describes a method for preparing a high-strength PE composite film, comprising the following steps: Step S1: 1.1 mol of sodium dimethyl isophthalate-5-sulfonate and 6.6 mol of 1,4-butanediol were added to a four-necked flask equipped with a stirrer, thermometer, gas delivery tube and distillation apparatus. Nitrogen gas was introduced for protection. The mixture was stirred at 145 r / min and heated to 180 °C at a rate of 2 °C / min. Then 0.66 g of zinc acetate dihydrate was added and the reaction was continued to be stirred for 3.1 h. After the reaction was completed, the mixture was naturally cooled to 85 °C. While still hot, the reaction solution was poured into anhydrous ethanol and stirred and cooled to room temperature. The mixture was then filtered and the filter cake was washed three times with anhydrous ethanol. The filter cake was transferred to a vacuum drying oven and vacuum dried at 57 °C for 12.5 h to obtain sodium sulfonate monomer. Step S2: Add 0.6 mol of dimethyl terephthalate and 1.44 mol of ethylene glycol to a reaction vessel equipped with a distillation apparatus. Replace the air in the vessel three times with nitrogen. Stir at 175 r / min and heat to 180°C at a rate of 2°C / min. Add 0.048 g of zinc acetate dihydrate and stir. When the collected methanol amount is ≥30 g, add 11.53 g of sodium sulfonyl butyrate monomer and continue stirring for 31 min. Add 0.038 g of antimony trioxide and stir for 16 min. Close the distillation channel and open the distillation valve. The temperature and pressure were initially increased in stages: the temperature was increased to 240℃ at a rate of 1℃ / min, while the pressure was reduced to 1kPa within 30min. The temperature was then increased to 275℃ at a rate of 1℃ / min, while the pressure was reduced to 100Pa within 1h. Finally, the pressure was reduced to below 10Pa within 30min. The reaction was carried out under constant temperature and pressure for 3h. After that, nitrogen gas was introduced to bring the pressure to atmospheric pressure. The mixture was then poured into cold water for quenching and cut into granules (3×3mm). The granules were then vacuum dried at 115℃ for 12.5h to obtain sulfobutyl isophthalate modified copolyester. Step S3: 1.1 mol adipic acid and 1760 g anhydrous ethanol were added to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred for 17 min at 27 °C and a stirring rate of 350 r / min. Then, 0.905 mol 2-methylpentanediamine and 0.25 mol m-phenylenediamine were added dropwise at a rate of 1 drop / s to achieve a pH of 7.7. After the addition was complete, the temperature was raised to 60 °C and the mixture was stirred for another 41 min. The mixture was then allowed to cool naturally to room temperature and allowed to stand for 2 h. The mixture was then filtered and the filter cake was washed three times with anhydrous ethanol. Finally, the mixture was placed in a vacuum drying oven and dried at 57 °C for 12.5 h to obtain methylpentanediamine-m-phenylenediamine adipate. Step S4: Add 210g of methylpentanediamine-m-phenylenediamine adipate, 52.5g of deionized water, and 0.105g of sodium hypophosphite to a high-pressure reactor. Replace the air in the reactor three times with nitrogen. Stir at 200 rpm and heat to 225°C at a rate of 2°C / min. React for 61 min, maintain the reactor temperature, open the exhaust valve to release pressure to atmospheric pressure, purge with nitrogen for 10 min, cool, and then place in a vacuum drying oven at 57°C for 12.5 h. The powder is then ready. The material was crushed through an 80-mesh sieve and then placed in a tubular reactor. After three purgings with nitrogen, the temperature was increased to 180°C at a rate of 1°C / min and held at that temperature for 61 min. The temperature was then increased to 195°C at a rate of 1°C / min and held at that temperature for 31 min. The nitrogen was then turned off, and the system was evacuated to ≤100 Pa and reacted for 6.2 h. After the reaction was completed, the system was kept under vacuum and cooled to room temperature. The material was then discharged and vacuum dried at 75°C for 25 h to obtain m-phenylenediamine modified methylpentanediamine adipamide. Step S5: Add 735g of high-density polyethylene (TAISOX® F200) and 315g of linear low-density polyethylene (SECCO® LL0220AA) to a high-speed mixer and mix for 2 minutes at 63°C and 900 r / min. Add 2.1g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2.1g of tris(2,4-di-tert-butylphenyl) phosphite and mix for 3 minutes. Add 3.15g of erucamide and 4.2g of silica and mix for 6 minutes. After mixing, release the material and cool it to below 40°C. Then, vacuum dry it at 80°C for 5 hours to obtain the matrix material. Step S6: Dry the sulfonated butyl isophthalate modified copolyester in a 120℃ vacuum drying oven for 14 hours; dry the isophthalamide modified methylpentanediamine adipamide in a 90℃ vacuum drying oven for 25 hours; dry the maleic anhydride grafted polyethylene (maleic anhydride grafted polyethylene model: Nanjing Sutai ST-6) in an 80℃ vacuum drying oven for 4.5 hours. Then, set the temperatures for each section according to Table 1, preheat the equipment by idling for 31 minutes, then install the filter screen, and add the materials to the corresponding extruder hoppers. The sulfobutyl isophthalate modified copolyester was placed in extruder No. 1. The first binder layer blend was prepared by drying maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene separately in a vacuum drying oven at 80°C for 4 hours. The dried maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene were weighed at a mass ratio of 90:10, and 0.2% of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine was added. Add all materials to a high-speed mixer and mix for 4 minutes at 60℃ and 800 r / min. Then, add the mixture to extruder No. 2. Add the m-phenylenediamine-modified methylpentanediamine adipyl polyamide to extruder No. 3. Add the maleic anhydride-grafted polyethylene to extruder No. 4. Add the matrix material to extruder No. 5. Initially, each extruder should run at a low speed of 17 r / min to discharge any remaining material. (After discharge, adjust the speed of each extruder to a total thickness of 50 μm, with extruder No. 1's speed corresponding to a layer thickness of 10 μm, and extruder No. 2's speed...) (The speed of extruder #3 corresponds to a layer thickness of 5μm, the speed of extruder #4 corresponds to a layer thickness of 5μm, and the speed of extruder #5 corresponds to a layer thickness of 20μm.) After that, casting begins, with the cooling roller temperature controlled at 27℃, the traction speed at 35m / min, and the winding tension at 17N / m to ensure a smooth film surface without stretching deformation. Then, the corona treatment machine is turned on to treat only the outer surface, with a treatment power of 800W and an electrode spacing of 1.8mm. After stable operation for 30 minutes, a high-strength PE composite film is obtained.
[0026] Example 3: This embodiment describes a method for preparing a high-strength PE composite film, comprising the following steps: Step S1: 1.2 mol of sodium dimethyl isophthalate-5-sulfonate and 7.2 mol of 1,4-butanediol were added to a four-necked flask equipped with a stirrer, thermometer, gas delivery tube and distillation apparatus. Nitrogen gas was introduced for protection. The mixture was stirred at 150 r / min and heated to 180 °C at a rate of 2 °C / min. Then 0.72 g of zinc acetate dihydrate was added and the reaction was continued to be stirred for 3.2 h. After the reaction was completed, the mixture was naturally cooled to 90 °C. While still hot, the reaction solution was poured into anhydrous ethanol and stirred and cooled to room temperature. The mixture was then filtered and the filter cake was washed three times with anhydrous ethanol. The filter cake was transferred to a vacuum drying oven and vacuum dried at 60 °C for 13 h to obtain sodium sulfonate monomer. Step S2: Add 0.7 mol of dimethyl terephthalate and 1.68 mol of ethylene glycol to a reaction vessel equipped with a distillation apparatus. Replace the air in the vessel three times with nitrogen. Stir at 180 r / min and heat to 180°C at a rate of 2°C / min. Add 0.056 g of zinc acetate dihydrate and stir. When the amount of methanol collected is ≥30 g, add 13.45 g of sodium sulfonyl butyrate monomer and continue stirring for 32 min. Add 0.045 g of antimony trioxide and stir for 17 min. Close the distillation channel and open the distillation valve. The temperature and pressure were initially increased in stages: the temperature was increased to 240℃ at a rate of 1℃ / min, while the pressure was reduced to 1kPa within 30min. The temperature was then increased to 275℃ at a rate of 1℃ / min, while the pressure was reduced to 100Pa within 1h. Finally, the pressure was reduced to below 10Pa within 30min. The reaction was carried out under constant temperature and pressure for 3.5h. After that, nitrogen gas was introduced to bring the pressure to atmospheric pressure. The mixture was then poured into cold water for quenching and cut into granules (3×3mm). The granules were then vacuum dried at 120℃ for 13h to obtain sulfobutyl isophthalate modified copolyester. Step S3: 1.2 mol adipic acid and 1920 g anhydrous ethanol were added to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred for 20 min at 30 °C and a stirring rate of 400 r / min. Then, 0.96 mol 2-methylpentanediamine and 0.3 mol m-phenylenediamine were added dropwise at a rate of 2 drops / s to achieve a pH of 7.8. After the addition was complete, the temperature was raised to 60 °C and the mixture was stirred for another 42 min. The mixture was then allowed to cool naturally to room temperature and allowed to stand for 2 h. The mixture was then filtered and the filter cake was washed three times with anhydrous ethanol. Finally, the mixture was placed in a vacuum drying oven and dried at 60 °C for 13 h to obtain methylpentanediamine-m-phenylenediamine adipate. Step S4: Add 220g of methylpentanediamine-m-phenylenediamine adipate, 55g of deionized water, and 0.11g of sodium hypophosphite to a high-pressure reactor. Replace the air in the reactor three times with nitrogen. Stir at 200 rpm and heat to 225°C at a rate of 2°C / min. React for 62 minutes, maintaining the reactor temperature. Release the pressure to atmospheric pressure by opening the exhaust valve, purge with nitrogen for 10 minutes, cool, and then place in a vacuum drying oven at 60°C for 13 hours. Grind the mixture. The sample was sieved through an 80-mesh sieve and then placed in a tubular reactor. After three purgings with nitrogen, the temperature was increased to 180°C at a rate of 1°C / min and held at that temperature for 62 min. The temperature was then increased to 195°C at a rate of 1°C / min and held at that temperature for 32 min. The nitrogen gas was then turned off, and the system was evacuated to ≤100 Pa and reacted for 6.5 h. After the reaction was completed, the system was kept under vacuum and cooled to room temperature. The sample was then discharged and vacuum dried at 80°C for 26 h to obtain m-phenylenediamine modified methylpentanediamine adipamide. Step S5: Add 770g of high-density polyethylene (TAISOX® F200) and 330g of linear low-density polyethylene (SECCO® LL0220AA) to a high-speed mixer and mix for 2 minutes at 65°C and 1000 r / min. Add 2.2g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2.2g of tris(2,4-di-tert-butylphenyl) phosphite and mix for 3 minutes. Add 3.3g of erucamide and 4.4g of silica and mix for 7 minutes. After mixing, release the material and cool it to below 40°C. Then, vacuum dry it at 80°C for 6 hours to obtain the matrix material. Step S6: Dry the sulfonated butyl isophthalate modified copolyester in a 120℃ vacuum drying oven for 16 hours; dry the isophthalamide modified methylpentanediamine adipamide in a 90℃ vacuum drying oven for 26 hours; dry the maleic anhydride grafted polyethylene (maleic anhydride grafted polyethylene model: Nanjing Sutai ST-6) in an 80℃ vacuum drying oven for 5 hours. Then, set the temperatures for each section according to Table 1, preheat the equipment by idling for 32 minutes, then install the filter screen and add the materials to the corresponding extruder hoppers. The butyl isophthalate modified copolyester was placed in extruder No. 1. The first binder layer blend (prepared by drying maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene separately in an 80℃ vacuum drying oven for 4 hours, weighing the dried maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene at a mass ratio of 90:10, and adding 0.2% of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine) The following materials were added to a high-speed mixer and mixed for 4 minutes at 60℃ and 800 r / min: m-phenylenediamine-modified methylpentanediamine adipyl polyamide was added to extruder No. 2; maleic anhydride-grafted polyethylene was added to extruder No. 4; and the matrix material was added to extruder No. 5. Each extruder was initially run at a low speed of 20 r / min to discharge residual material. (After discharge, the speed of each extruder was adjusted to a total thickness of 50 μm, with the speed of extruder No. 1 corresponding to a layer thickness of 10 μm, and the speed of extruder No. 2...) (Corresponding to a layer thickness of 5μm, the speed of extruder No. 3 corresponds to a layer thickness of 10μm, the speed of extruder No. 4 corresponds to a layer thickness of 5μm, and the speed of extruder No. 5 corresponds to a layer thickness of 20μm.) After that, casting begins, with the cooling roller temperature controlled at 30℃, the traction speed at 40m / min, and the winding tension at 20N / m to ensure a smooth film surface without stretching deformation. Then, the corona treatment machine is turned on to treat only the outer surface, with a treatment power of 800W and an electrode spacing of 1.8mm. After stable operation for 30 minutes, a high-strength PE composite film is obtained.
[0027] Comparative Example 1: This comparative example describes a method for preparing a high-strength PE composite film, comprising the following steps: Step S1: Add 1 mol of adipic acid and 1600 g of anhydrous ethanol to a three-necked flask equipped with a stirrer, thermometer, constant pressure dropping funnel and gas delivery tube. Purge with nitrogen for protection and stir for 15 min at 25 °C and 300 r / min. Then, add 0.96 mol of 2-methylpentanediamine and 0.3 mol of m-phenylenediamine dropwise at a rate of 1 drop / s to achieve a pH of 7.6. After the addition is complete, raise the temperature to 60 °C and continue stirring for 40 min. Allow to cool naturally to room temperature and stand for 2 h. Filter the mixture and wash the filter cake three times with anhydrous ethanol. Then place it in a vacuum drying oven and dry at 55 °C for 12 h to obtain methylpentanediamine-m-phenylenediamine adipate. Step S2: Add 200g of methylpentanediamine-m-phenylenediamine adipate, 50g of deionized water, and 0.10g of sodium hypophosphite to a high-pressure reactor. Replace the air in the reactor three times with nitrogen. Stir at 200 rpm and heat to 225°C at a rate of 2°C / min. React for 60 minutes, maintaining the reactor temperature. Release the pressure to atmospheric pressure by opening the exhaust valve, purge with nitrogen for 10 minutes, and then cool. Place the reactor in a vacuum drying oven and dry at 55°C for 12 hours. Pulverize. After passing through an 80-mesh sieve, the sample was placed in a tubular reactor and purged with nitrogen three times. The temperature was then increased to 180°C at a rate of 1°C / min and held at that temperature for 60 min. The temperature was then increased to 195°C at a rate of 1°C / min and held at that temperature for 30 min. The nitrogen gas was then turned off, and the system was evacuated to ≤100 Pa and reacted for 6 h. After the reaction was completed, the sample was cooled to room temperature while maintaining a vacuum. The sample was then discharged and vacuum dried at 70°C for 24 h to obtain m-phenylenediamine modified methylpentanediamine adipamide. Step S3: Add 700g of high-density polyethylene (TAISOX® F200) and 300g of linear low-density polyethylene (SECCO® LL0220AA) to a high-speed mixer and mix for 2 minutes at 60°C and 800 r / min. Add 2.0g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2.0g of tris(2,4-di-tert-butylphenyl) phosphite and mix for 3 minutes. Add 3.0g of erucamide and 4g of silica and mix for 5 minutes. After mixing, release the material and cool it to below 40°C. Then, vacuum dry it at 80°C for 4 hours to obtain the matrix material. Step S4: Dry the m-phenylenediamine-modified methylpentanediamine adipamide in a 90℃ vacuum drying oven for 24 hours. Dry the maleic anhydride-grafted polyethylene (maleic anhydride-grafted polyethylene model: Nanjing Sutai ST-6) in an 80℃ vacuum drying oven for 4 hours. Then, set the temperatures for each section according to Table 1. Preheat the equipment by idling for 30 minutes. After that, install the filter screen and add the materials to the corresponding extruder hoppers. Put the m-phenylenediamine-modified methylpentanediamine adipamide into extruder No. 1, the maleic anhydride-grafted polyethylene into extruder No. 2, and the matrix material into extruder No. 3. Initially, each extruder starts at 15 r / min. After running at low speed for 30 minutes to remove residual material, (after discharge, adjust the speed of each extruder to a total thickness of 50μm, with the speed of extruder 1 corresponding to a layer thickness of 10μm, extruder 2 corresponding to a layer thickness of 10μm, and extruder 3 corresponding to a layer thickness of 30μm) then begin casting. Control the temperature of the cooling roller at 25℃, the traction speed at 30m / min, and the winding tension at 15N / m to ensure a smooth film surface without stretching deformation. Then, turn on the corona treatment machine to treat only the outer surface, with a treatment power of 800W and an electrode spacing of 1.8mm. Run stably for 30 minutes to obtain a high-strength PE composite film.
[0028] Comparative Example 2: This comparative example describes a method for preparing a high-strength PE composite film, comprising the following steps: Step S1: 1 mol of sodium dimethyl isophthalate-5-sulfonate and 6 mol of 1,4-butanediol were added to a four-necked flask equipped with a stirrer, thermometer, gas delivery tube and distillation apparatus. Nitrogen gas was introduced for protection. The mixture was stirred at 140 r / min and heated to 180 °C at a rate of 2 °C / min. Then 0.6 g of zinc acetate dihydrate was added and the mixture was stirred and reacted for 3 h. After the reaction was completed, the mixture was allowed to cool naturally to 80 °C. While still hot, the reaction solution was poured into anhydrous ethanol and stirred and cooled to room temperature. The mixture was then filtered and the filter cake was washed three times with anhydrous ethanol. The filter cake was transferred to a vacuum drying oven and dried under vacuum at 55 °C for 12 h to obtain sodium sulfonate monomer. Step S2: Add 0.5 mol of dimethyl terephthalate and 1.20 mol of ethylene glycol to a reaction vessel equipped with a distillation apparatus. Replace the air in the vessel three times with nitrogen. Stir at 170 r / min and heat to 180°C at a rate of 2°C / min. Add 0.040 g of zinc acetate dihydrate and stir. When the collected methanol amount is ≥30 g, add 9.61 g of sodium sulfonyl butyrate monomer and continue stirring for 30 min. Add 0.032 g of antimony trioxide and stir for 15 min. Close the distillation channel and open the distillation valve. The temperature and pressure were initially increased in stages: the temperature was increased to 240℃ at a rate of 1℃ / min, while the pressure was reduced to 1kPa within 30min. The temperature was then increased to 275℃ at a rate of 1℃ / min, while the pressure was reduced to 100Pa within 1h. Finally, the pressure was reduced to below 10Pa within 30min. The reaction was carried out under constant temperature and pressure for 2.5h. After that, nitrogen gas was introduced to bring the pressure to atmospheric pressure. The mixture was then poured into cold water for quenching and cut into granules (3×3mm). The granules were then vacuum dried at 110℃ for 12h to obtain sulfobutyl isophthalate modified copolyester. Step S3: Add 700g of high-density polyethylene (TAISOX® F200) and 300g of linear low-density polyethylene (SECCO® LL0220AA) to a high-speed mixer and mix for 2 minutes at 60°C and 800 r / min. Add 2.0g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2.0g of tris(2,4-di-tert-butylphenyl) phosphite and mix for 3 minutes. Add 3.0g of erucamide and 4g of silica and mix for 5 minutes. After mixing, release the material and cool it to below 40°C. Then, vacuum dry it at 80°C for 4 hours to obtain the matrix material. Step S4: Place the sulfobutyl isophthalate modified copolyester in a 120℃ vacuum drying oven and dry for 12 hours. Place the maleic anhydride-grafted polyethylene (maleic anhydride-grafted polyethylene model: Nanjing Sutai ST-6) in an 80℃ vacuum drying oven and dry for 4 hours. Then, set the temperature of each section according to Table 1, preheat the equipment by idling for 30 minutes, then install the filter screen, and add the materials to the corresponding extruder hoppers. Place the sulfobutyl isophthalate modified copolyester into extruder No. 1. The first binder layer blend (the preparation of the first binder layer blend is to place maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene in an 80℃ vacuum drying oven and dry for 4 hours respectively, weigh the dried maleic anhydride-grafted polyethylene and glycidyl methacrylate-grafted polyethylene at a mass ratio of 90:10, and add N,N'-bis[β-(3, [5-Di-tert-butyl-4-hydroxyphenyl]propionylhydrazine was added to a high-speed mixer and mixed for 4 minutes at 60°C and 800 r / min. The mixture was then fed into extruder No. 2, and the matrix material was fed into extruder No. 3. Each extruder was initially run at a low speed of 15 r / min to remove residual material. After discharge, the speed of each extruder was adjusted to a total thickness of 50 μm, with the speed of extruder No. 1 corresponding to a layer thickness of 10 μm, the speed of extruder No. 2 corresponding to a layer thickness of 10 μm, and the speed of extruder No. 3 corresponding to a layer thickness of 30 μm. Then, casting was started, with the cooling roller temperature controlled at 25°C, the traction speed at 30 m / min, and the winding tension at 15 N / m to ensure a smooth film surface without stretching deformation. After that, the corona treatment machine was turned on to treat only the outer surface, with a treatment power of 800 W and an electrode spacing of 1.8 mm. The mixture was run stably for 30 minutes to obtain a high-strength PE composite film.
[0029] Comparative Example 3: This comparative example describes a method for preparing a high-strength PE composite film, comprising the following steps: Step S1: Add 700g of high-density polyethylene (TAISOX® F200) and 300g of linear low-density polyethylene (SECCO® LL0220AA) to a high-speed mixer and mix for 2 minutes at 60°C and 800 r / min. Add 2.0g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2.0g of tris(2,4-di-tert-butylphenyl) phosphite and mix for 3 minutes. Add 3.0g of erucamide and 4g of silica and mix for 5 minutes. After mixing, release the material and cool it to below 40°C. Then, vacuum dry it at 80°C for 4 hours to obtain the matrix material. Step S2: Dry the maleic anhydride-grafted polyethylene (model: Nanjing Sutai ST-6) in an 80℃ vacuum drying oven for 4 hours. Then, set the temperature of each section according to Table 1, preheat the equipment by idling for 30 minutes, then install the filter screen. Add the two materials to the corresponding extruder hoppers. Put the maleic anhydride-grafted polyethylene into extruder No. 1 and the matrix material into extruder No. 2. Initially, run each extruder at a low speed of 15r / min to discharge residual material. (Adjust after discharge) Each extruder was rotated to a total thickness of 50μm (extruder 1's rotation speed corresponds to a layer thickness of 10μm, and extruder 2's rotation speed corresponds to a layer thickness of 40μm). Then, casting began. The cooling roller temperature was controlled at 25℃, the traction speed at 30m / min, and the winding tension at 15N / m to ensure a smooth film surface without stretching deformation. After that, the corona treatment machine was turned on to treat only the outer surface. The treatment power was 800W, the electrode spacing was 1.8mm, and the machine was run stably for 30min to obtain a high-strength PE composite film.
[0030] Performance testing: The high-strength PE composite films of Examples 1-3 and Comparative Examples 1-3 were tested according to the following methods; Longitudinal and transverse tensile strength tests: The tests were conducted in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets". The total length of the specimen was 150 mm, the width of the parallel section was 15 mm, and the gauge length was 50 mm. At least 5 parallel specimens were cut along both the longitudinal and transverse directions of the composite film. The edges of the specimens should be smooth and without gaps. A universal testing machine was used with an initial clamping distance of 100 mm and a tensile speed of 100 mm / min. The arithmetic mean of the longitudinal and transverse tensile strengths was calculated.
[0031] Oxygen permeability test: The test shall be conducted in accordance with GB / T 1038.1-2022 "Test methods for gas permeability of plastic films and sheets - Part 1: Differential pressure method". At least three circular specimens with a diameter of 97 mm shall be cut, and the effective test area shall be 38.48 cm². 2 The sample surface should be free of defects such as pinholes, wrinkles, and scratches. The test temperature is 23℃, the relative humidity of the test environment is 50%, and the pressure difference between the upper and lower chambers is 0.1MPa. Calculate the arithmetic mean of the oxygen permeability.
[0032] Water vapor transmission rate test: The test was conducted according to GB / T 1037-2021 "Determination of Water Vapor Transmission Performance of Plastic Films and Sheets - Cup Method (Gain and Loss Method)". At least three circular samples with a diameter of 97 mm were cut, and the effective test area was 38.48 cm². 2The test temperature was 38℃, the relative humidity inside the test cup was 90% (adjusted with saturated potassium chloride solution), and anhydrous calcium chloride desiccant with a particle size of 2mm was placed inside the test cup. The distance between the surface of the desiccant and the lower surface of the sample was not less than 10mm. After continuous weighing until the mass change was constant, the arithmetic mean of the water vapor transmission rate was calculated.
[0033] Heat seal strength test: The test shall be conducted in accordance with QB / T 2358-1998 "Test method for heat seal strength of plastic film packaging bags". No less than 5 samples with a width of 15mm and a length of 100mm shall be cut. The samples shall be flat and free from deformation. Double-sided heat sealing shall be adopted. The heat sealing temperature shall be 130℃, the heat sealing pressure shall be 0.2MPa, the heat sealing time shall be 1s, and the heat sealing width shall be 10mm. After heat sealing, the samples shall be placed in a standard environment for 1 hour before testing. The universal testing machine shall be used with a clamp spacing of 100mm and a tensile speed of 300mm / min. The arithmetic mean of the heat seal strength shall be calculated.
[0034] The test results are shown in Table 2: Table 2: Test Results Summary Table
[0035] Referring to Table 2, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the high-strength PE composite film has ultra-high mechanical strength, excellent oxygen and water vapor barrier properties, excellent interlayer adhesion stability, and reliable heat-sealing performance.
[0036] A comparison of Examples 1-3 shows that from Example 1 to Example 3, the transesterification and polycondensation reaction time, vacuum polycondensation time, drying time, equipment preheating time, as well as the extruder speed, cooling roller temperature, traction speed, and winding tension are all gradually increased. This makes the polymerization reaction more complete, the removal of moisture and small molecule byproducts more thorough, and the molecular weight and density of polyester and polyamide better. At the same time, the plasticization uniformity, interlayer adhesion, and film surface smoothness during five-layer co-extrusion are better, and there are fewer defects. Therefore, Example 3 has slightly better overall performance, followed by Example 2, and Example 1 is relatively lower, but the overall difference among the three should be small.
[0037] Based on the comparison between Example 1 and Comparative Example 1, it can be seen that the reinforcing outer layer is the core supporting structure for the mechanical strength of the composite film. Under the premise of keeping the barrier performance and heat sealing performance basically unchanged, the longitudinal tensile strength and transverse tensile strength of the composite film are significantly improved after adding the sulfobutyl isophthalate modified copolyester reinforcing outer layer.
[0038] Based on the comparison between Example 1 and Comparative Example 2, it can be seen that the m-phenylenediamine modified methylpentanediamine adipamide barrier layer is a necessary structure to achieve high barrier performance. Under the premise of maintaining stable heat sealing performance, the oxygen permeability and water vapor permeability of the composite film are reduced after adding this barrier layer, and the barrier layer also contributes to the mechanical strength of the composite film.
[0039] Based on the comparison between Example 1 and Comparative Example 3, it can be seen that the reinforcing outer layer and the barrier layer have a significant synergistic effect. When both core structures are missing at the same time, the overall performance of the composite membrane decreases significantly, proving that the reinforcing outer layer and the barrier layer form a uniformly stressed and structurally complete whole through the adhesive layer, which together determines the high strength and high barrier properties of the composite membrane.
[0040] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0041] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A high-strength PE composite film, characterized in that, It adopts a five-layer structure, from the outside to the inside: reinforcing outer layer, first adhesive layer, barrier layer, second adhesive layer and heat-sealing inner layer; The outer reinforcing layer is made of sulfobutyl isophthalate modified copolyester; the first adhesive layer is made of a first adhesive layer blend; the barrier layer is made of isophthalamide modified methylpentanediamine adipamide polyamide; the second adhesive layer is made of maleic anhydride grafted polyethylene; and the heat-sealing inner layer is made of a matrix material. The sulfonated butyl isophthalate modified copolyester is prepared by the following steps: Step a1: Sodium dimethyl isophthalate-5-sulfonate and 1,4-butanediol are mixed, and then zinc acetate dihydrate is added. The reaction is stirred and the reaction is continued. The reaction solution is poured into anhydrous ethanol, stirred and cooled, filtered, washed, and dried under vacuum to obtain sodium sulfobutyl ester monomer. Step a2: Dimethyl terephthalate and ethylene glycol are added to a reaction vessel, zinc acetate dihydrate is added and stirred to react, sodium sulfobutyl ester monomer is added and stirred again, antimony trioxide is added and stirred, the temperature and pressure are increased in stages and then the reaction is carried out at constant temperature and pressure, nitrogen gas is introduced to reach atmospheric pressure, the mixture is poured into cold water for quenching, cut into granules, and vacuum dried to obtain sulfobutyl isophthalate modified copolyester; The m-phenylenediamine-modified methylpentanediamine adipamide was prepared by the following steps: Step b1: Add adipic acid and anhydrous ethanol to a three-necked flask and stir to react. Then, add 2-methylpentanediamine and m-phenylenediamine dropwise together, heat and continue stirring to react. Cool, let stand, filter, wash, and then dry to obtain methylpentanediamine-m-phenylenediamine adipate. Step b2: Methylpentanediamine-m-phenylenediamine adipate, deionized water and sodium hypophosphite are added to a high-pressure reactor for reaction. After that, the pressure is released to atmospheric pressure, cooled, dried, pulverized and sieved. Then it is placed in a tubular reactor for constant temperature reaction, vacuumed and reacted, cooled, discharged and vacuum dried to obtain m-phenylenediamine modified methylpentanediamine adipamide.
2. The high-strength PE composite film according to claim 1, characterized in that, In step a1, the ratio of sodium dimethyl isophthalate-5-sulfonate, 1,4-butanediol, and zinc acetate dihydrate is 1-1.2 mol: 6-7.2 mol: 0.6-0.72 g.
3. The high-strength PE composite film according to claim 1, characterized in that, In step a2, the ratio of dimethyl terephthalate, ethylene glycol, zinc acetate dihydrate, sodium sulfobutyl ester monomer, and antimony trioxide is 0.5-0.7 mol: 1.20-1.68 mol: 0.040-0.056 g: 9.61-13.45 g: 0.032-0.045 g.
4. The high-strength PE composite film according to claim 1, characterized in that, In step b1, the ratio of adipic acid, anhydrous ethanol, 2-methylpentanediamine, and m-phenylenediamine is 1-1.2 mol: 1600-1920 g: 0.85-0.96 mol: 0.2-0.3 mol.
5. A high-strength PE composite film according to claim 1, characterized in that, In step b2, the ratio of methylpentanediamine-m-phenylenediamine adipate, deionized water, and sodium hypophosphite is 200-220g: 50-55g: 0.10-0.11g.
6. The high-strength PE composite film according to claim 1, characterized in that, The matrix material is prepared by the following steps: High-density polyethylene and linear low-density polyethylene were mixed in a high-speed mixer, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite were added and mixed. Erucamide and silica were added and mixed. The mixture was cooled and then vacuum dried to obtain the matrix material.
7. A high-strength PE composite film according to claim 6, characterized in that, The ratio of high-density polyethylene, linear low-density polyethylene, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(2,4-di-tert-butylphenyl)phosphite, erucamide, and silica is 700-770g: 300-330g: 2.0-2.2g: 2.0-2.2g: 3.0-3.3g: 4-4.4g.
8. A method for preparing a high-strength PE composite film, characterized in that, The preparation of the high-strength PE composite film as described in any one of claims 1-7 includes the following steps: The sulfonated butyl isophthalate modified copolyester, isophthalamide modified methylpentanediamine adipamide, and maleic anhydride grafted polyethylene are dried. Then, the temperature of each section is set, and the equipment is preheated by idling. The materials are added to the corresponding extruder hoppers. Each extruder initially runs at low speed to discharge residual materials. Then, casting begins. After that, the corona treatment machine is turned on to treat only the outer surface. Stable operation is maintained to obtain a high-strength PE composite film.
9. The method for preparing a high-strength PE composite film according to claim 8, characterized in that, The materials were added to the corresponding extruder hoppers respectively. Specifically, the sulfobutyl isophthalate modified copolyester was placed in extruder No. 1, the first binder layer blend was placed in extruder No. 2, the isophthalamide modified methylpentanediamine adipyl polyamide was placed in extruder No. 3, the maleic anhydride grafted polyethylene was placed in extruder No. 4, and the matrix material was placed in extruder No.
5. The first binder layer blend was prepared by weighing dried maleic anhydride grafted polyethylene and glycidyl methacrylate grafted polyethylene at a mass ratio of 90:10, adding N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, and mixing.
